Conchomeatoplasty - ventilatory implications - Van Schalkwyk, Cornelis Rudolf (My University, 2014)
Chronic or recurrent otitis externa is a problematic entity for clinicians to control. One of the contributing causes to this problem is poor ventilation of the external auditory canal leading to high humidity and consequent maceration of the canal skin. Over the years several surgical procedures have been developed to widen the external auditory canal and therefore improve ventilation. Clinically these procedures have been quite successful in controlling chronic otitis externa. The improvement has always been ascribed to improved ventilation. This increase in ventilation has, however, never been documented, nor quantified. One of the successful procedures is that of conchomeatoplasty. This study set out to demonstrate an improvement in ventilation and if possible to quantify this improvement, following conchomeatoplasty. The operation was performed on thirty consecutive cadaver specimens and preoperative as well as postoperative measurements of the external ear canals were performed. Silicone moulds of the canals were taken and sectioned in an identical manner to obtain the required measurements. Statistical analysis demonstrated a consistent increase in canal diameter and by applying Poiseuille's equation to the results it was possible to demonstrate a five fold increase in the ventilatory capacity of the lateral external auditory canal at one of the narrowest points of the cartilaginous canal. This is the first documentation of improved ventilation following any type of meatoplasty. The method that was developed for measuring and comparing external canal sizes is unique and original and will allow for future comparison of different surgical techniques in an objective and scientific manner.